Effect of Competence, Organizational Culture, and Motivation towards Employee Performance at PT Kukuh Tangguh Sandang Mills - Yayan Sudaryana (Jurnal Ekonomi dan Bisnis Jagaditha, 2021)
Human resources are an element that will determine the achievement of goals effectively and efficiently. Employee performance is one of the main factors that can affect the progress of an organization or company. This study is intended to identify the extent of competence, organizational culture, and motivation that impress the employee performance at PT Kukuh Tangguh Sandang Mills in Bandung. This kind of causality research underlies in providing explanations and measuring the causal effect and quantitative research approach. Determining the number of samples using the Slovin' calculation formula with a precision of 10 percent to obtain a sample of 76 respondents. Data analysis techniques in this study using the aid of the SPSS for Windows Program. According to the results and discussion on the influence of competence, organizational culture, and motivation on employee performance, it can be concluded that the three determinants simultaneously and partially have a significant positive effect on employee performance. The value of the coefficient of determination was 49.3 percent, which gave a high contribution, namely competence, organizational culture, and motivation to employee performance at PT. Kukuh Tangguh Sandang Mills, Bandung.